The Impact of a Pre-Questioning Technique on Students' Reading Comprehension at a Bengkulu State Junior High School - Riswanto Riswanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the achievement of students' reading ability scores after using the pre-question and answer technique. The method used in this research is a quasi-experimental research method. The population of this research is the eighth-grade students of a Junior High School in Bengkulu. The sample consisted of 20 students in class VIII A as the experimental class and 20 students in class VIII C as the control class. The experimental class was taught using pre-questioning techniques and the control class was taught using discovery learning. The instruments used in this study were pre-test and post-test on descriptive text. The results of this study showed differences in learning outcomes of 82.75 for the experimental class and 80.00 for the control class. The data were analyzed using the t-test formula. sig value. (2-tailed) is 0.000 0.05. It can be concluded that the Null Hypothesis (H0) is rejected and the Alternative Hypothesis (Ha) is accepted. The results of this study have shown that the use of pre-questioning techniques can have a positive influence on improving students' reading comprehension in the eighth grade of SMPN 06 Seluma in the 2021/2022 academic year.